2019
DOI: 10.1590/1413-812320182410.26732017
|View full text |Cite
|
Sign up to set email alerts
|

Comportamientos de riesgo de suicidio y calidad de vida relacionada con la salud en estudiantes que ingresaron a una universidad mexicana

Abstract: Resumen El objetivo fue determinar si existe asociación entre comportamientos de riesgo de suicidio (CRS) y menor calidad de vida relacionada con la salud (CVRS) y si esta asociación es independiente del consumo de sustancias, violencia y variables sociodemográficas. Estudio transversal, con 1229 estudiantes universitarios mexicanos; 62.4% mujeres y 37.6% hombres, edad 18.2 ± .6 años. Se aplicaron los instrumentos YRBS y KIDSCREEN-52. Presentaron desesperanza 14.2%, ideación suicida (IS) 4.7%, planeación suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
3
0
2
Order By: Relevance
“…54 In the second study, the HRQoL was examined with the KIDSCREEN-52 in 1229 students aged 14 to 18 years (M = 15.45, SD = .87); having low levels of support from parents, family and friends increases suicidal ideation, while suicidal planning is related to a low score on physical and psychological well-being tests, which indicates a relationship between the construct of suicidal behaviors and HRQoL. 55…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 In the second study, the HRQoL was examined with the KIDSCREEN-52 in 1229 students aged 14 to 18 years (M = 15.45, SD = .87); having low levels of support from parents, family and friends increases suicidal ideation, while suicidal planning is related to a low score on physical and psychological well-being tests, which indicates a relationship between the construct of suicidal behaviors and HRQoL. 55…”
Section: Discussionmentioning
confidence: 99%
“…54 In the second study, the HRQoL was examined with the KIDSCREEN-52 in 1229 students aged 14 to 18 years (M = 15.45, SD = .87); having low levels of support from parents, family and friends increases suicidal ideation, while suicidal planning is related to a low score on physical and psychological well-being tests, which indicates a relationship between the construct of suicidal behaviors and HRQoL. 55 The negative association between the dimensions of QoL and suicidal behavior found in this study coincides with the motivational-volitional theory of suicidal behavior, which states that such behavior is motivated both by poor functioning and by stressful events in the environment that are combined with and triggered by feelings of defeat, humiliation, betrayal, lack of support or painful feelings. 56 As expected, depressive symptoms mediated the direct relationship between QoL and suicidal behavior, considering the antecedents of 3 studies that found a relationship between depressive symptoms and suicidal ideation; 1 of these studies was conducted with 1285 Mexican adolescents aged 12 to 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Internacionalmente, entre os estudantes do ensino médio 2,[32][33][34][35] , observaram-se valores entre 4,1% na cidade de Tabriz, Iran 32 , e 21,8% em Hong Kong, China 35 . No ensino superior 6,[36][37][38][39][40] , as prevalências estiveram entre 4,7%, em estudo com mexicanos 36 , e 31%, em Boyacá, Colômbia 38 . No Brasil, nos estudos referentes ao ensino médio 11,14,16,41 , a ideação suicida variou de 7,9%, em Teresina (Piauí) 14 , a 14%, em Aracaju e região metropolitana do estado de Sergipe 11 .…”
Section: Discussionunclassified
“…Likewise, young people with poor SS have up to 2.57 times the risk of SI (Asfaw et al, 2020). Poor communication with parents and in family life increases suicide risk up to 3.9 times (Hidalgo-Rasmussen et al, 2019). Conversely, having SS, good family relationships, positive communication with one's parents and the support of friends, has proved to be associated with a lower risk of suicide (Camargo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%